Immature stages of three species of Inca LePeletier & Serville, 1828 (Coleoptera: Scarabaeidae: Cetoniinae) and morphology of phytophagous scarab beetle pupa - Sousa, Rafael; Fuhrmann, Juares; Kouklík, Ondřej; Šípek, Petr (Zootaxa, 2018)
Immature stages of I. pulverulenta (Olivier, 1789) (Coleoptera: Scarabaeidae: Cetoniinae: Incini) are described for the first time, and those of I. bonpalandi (Gyllenhal, 1827) and I. clathrata sommeri Westwood, 1845 are redescribed. A key to the third instar of Incini is presented, notes on Inca larval characters in the phylogenetic context of Cetoniinae and on scarab pupal morphology are also given.